Intraperitoneal-Free Cancer Cells Represent a Major Prognostic Factor in Colorectal Peritoneal Carcinomatosis. Issue 7 (July 2016) - Trilling, B.; Cotte, E.; Vaudoyer, D.; Isaac, S.; Piaton, E.; Maurice, C.; Glehen, O.; Passot, G.
Abstract : BACKGROUND: Intraperitoneal-free cancer cells are considered as an important prognostic tool in gastric and ovarian cancer. However, their significance in colorectal cancer remains more controversial. OBJECTIVE: This study aimed to determine the role of intraperitoneal-free cancer cells as a prognostic tool in the outcome in colorectal peritoneal carcinomatosis treated with curative intent by complete cytoreductive surgery. DESIGN: This study is an analysis of a prospectively maintained database. PATIENTS: Between 1991 and 2012, all patients treated in a single institution for colorectal peritoneal carcinomatosis by complete cytoreductive surgery with peritoneal cytology available were evaluated. Peritoneal cytology was stained in the conventional way (May Grumwald Giemsa). RESULTS: Among a population of 162 patients treated for colorectal peritoneal carcinomatosis by complete cytoreductive surgery, 38 presented positive intraperitoneal-free cancer cells (23.5%). Systemic chemotherapy was administered to 135 patients (85%) during the preoperative course. Median follow-up was 34.5 months. Median overall survival was 19 and 44 months for positive and negative intraperitoneal-free cancer cells ( p = 0.018). In multivariate analysis, Peritoneal Carcinomatosis Index and positive intraperitoneal-free cancer cells were significant prognostic factors of overall survival (HR, 2.3 (1.18–4.52), p = 0.014; HR, 1.9 (1.08–3.38), p = 0.027). LIMITATIONS: Retrospective analysis and the long period were limitations of study. CONCLUSION: Along with the Peritoneal Carcinomatosis Index, intraperitoneal-free cancer cells are a strong prognostic factor for patients treated with curative intent for colorectal peritoneal carcinomatosis by complete cytoreductive surgery. The presence of intraperitoneal-free cancer cells should lead to the consideration of different treatment strategies such as extensive intraperitoneal lavage, targeted intraperitoneal therapies, or repeated intraperitoneal chemotherapy.